2017
DOI: 10.1016/j.cogpsych.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Learning to allocate limited time to decisions with different expected outcomes

Abstract: The goal of this article is to investigate how human participants allocate their limited time to decisions with different properties. We report the results of two behavioral experiments. In each trial of the experiments, the participant must accumulate noisy information to make a decision. The participants received positive and negative rewards for their correct and incorrect decisions, respectively. The stimulus was designed such that decisions based on more accumulated information were more accurate but took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 74 publications
(118 reference statements)
1
12
0
Order By: Relevance
“…In a modeling framework, optimizing this trade-off between the speed and accuracy with which we make decisions can be implemented through a decision threshold that specifies the amount of evidence that is required for making a choice [13]. It has been inferred from behavioral data that humans may adjust their decision threshold on the basis of both the instruction to be fast or accurate given before a task [4, 5] and the difficulty of the decision to be made as the task unfolds [68]. The process of adjusting the decision threshold according to task difficulty was recently investigated in a behavioral study, which suggested that humans determine the difficulty of the current decision after a brief period of integrating evidence, and only then adjust the decision threshold in a single abrupt change [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a modeling framework, optimizing this trade-off between the speed and accuracy with which we make decisions can be implemented through a decision threshold that specifies the amount of evidence that is required for making a choice [13]. It has been inferred from behavioral data that humans may adjust their decision threshold on the basis of both the instruction to be fast or accurate given before a task [4, 5] and the difficulty of the decision to be made as the task unfolds [68]. The process of adjusting the decision threshold according to task difficulty was recently investigated in a behavioral study, which suggested that humans determine the difficulty of the current decision after a brief period of integrating evidence, and only then adjust the decision threshold in a single abrupt change [6].…”
Section: Introductionmentioning
confidence: 99%
“…One way to compare these models is to treat BIC/AIC as the log model evidence for each participant and investigate if there is a significant difference between the BIC (AIC) for a pair of models, Khodadadi et al (2017). However, this needs many pairwise comparisons.…”
Section: Model Fit Results In the Learning (Training) Blocksmentioning
confidence: 99%
“…Reinforcement learning models (Busemeyer and Stout, 2002;Sutton & Barton, 1998), for instance, have successfully been used to explain the acquisition of optimal decision policies in value-based decisionmaking (e.g., Ahn et al (2008), Fridberg et al (2010), and Steingroever et al (2014)). Such a combined model, as suggested by Khodadadi et al (2017), would allow researchers to account for factors such as incomplete exploration, and help quantify the degree of RR-optimality human decision-makers can achieve within a given time frame.…”
Section: Discussionmentioning
confidence: 99%